Programas de trainee como propulsores de carreira internacional - Loureiro Junior, Leonardo Godóes (2021)
The present study aims to comprehend to which extent is possible to establish a relation between the young talents selected in trainee programs offered by global companies and the construction of an international career. For this purpose, it will be done a theoretical background regarding the development of a career in contemporaneity, about the processes since the application to the development in the trainee program and about the expatriation. An empirical exploratory research was carried out, with a qualitative approach, through interviews held with young trainees and expatriates of different companies to identify the possible relation between the investment in a hard selection process as the trainee with the development of an nternational career. As a result, the trainee program could help the young professional to have expertise and a career acceleration that assists and promotes their exposure, but if they do not show interest for their superior and do not create a rich network it may not contribute to this desired international career.